2009
DOI: 10.1038/ijo.2009.152
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in regulatory pathways of fatty acid and glucose metabolism are associated with obesity phenotypes: a population-based cohort study

Abstract: Background: As nuclear receptors and transcription factors have an important regulatory function in adipocyte differentiation and fat storage, genetic variation in these key regulators and downstream pathways may be involved in the onset of obesity. Objective: To explore associations between single nucleotide polymorphisms (SNPs) in candidate genes from regulatory pathways that control fatty acid and glucose metabolism, and repeated measurements of body mass index (BMI) and waist circumference in a large Dutch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 57 publications
1
26
3
Order By: Relevance
“…The present study selected subjects from the ongoing Doetinchem cohort (Lu et al 2008;van den Berg et al 2009). The design of the Doetinchem study and detailed methods have been reported earlier (Verschuren et al 2008).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study selected subjects from the ongoing Doetinchem cohort (Lu et al 2008;van den Berg et al 2009). The design of the Doetinchem study and detailed methods have been reported earlier (Verschuren et al 2008).…”
Section: Study Populationmentioning
confidence: 99%
“…At the start of the study, a blood sample was drawn, fractionated to obtain buffy coats for isolation of DNA and subsequently stored at -30°C. DNA isolation, SNP selection and genotyping Genomic DNA was isolated from stored buffy coats using a salting out method as described before (van den Berg et al 2009). To ensure a considerable fraction of carriers of the minor allele, only SNPs with a minor allele frequency in Europeans of at least 25 %, as indicated in the SNP public database (dbSNP; http://www.ncbi.nlm.nih.gov/SNP), were considered as candidates.…”
Section: Study Populationmentioning
confidence: 99%
“…Inclusion criteria for genetic studies were stable smoking behavior and absence of pregnancy at time of measurement as described previously. 9 Data from four visit rounds are now available. However, waist circumference was not assessed in the first measurement round.…”
Section: Study Populationsmentioning
confidence: 99%
“…All yielded the same results, except for two SNPs, which were, therefore, excluded. 16 Thus, data on 353 SNPs in 239 genes were available for 3244 participants.…”
Section: Genotypingmentioning
confidence: 99%